Reaction engineering of urea alcoholysis: alkyl carbamates - Mote, Dhananjay R.; Ranade, Vivek V. (Indian Journal of Chemical Technology, 2017)
Urea alcoholysis is a reversible reaction generating alkyl carbamate and ammonia as products. The reaction can be performed non-catalytically or in presence of catalyst. The first step in Reaction engineering analysis is to finalize the reactor configuration. In this case it is important to determine the necessity of reactive separation (simultaneous reaction and separation). This has been addressed by first establishing the reversibility of the reaction through theoretical and experimental investigation. Based on this analysis, an experimental setup comprising tubular reactor and a separator has been built. Experiments have been performed for different alcohols at different flow rates and temperatures. The experimental data is used to establish kinetic parameters. Systematic reaction engineering analysis based on multi-stage ideal reactors with and without simultaneous mass transfer is then carried out in terms of three dimensionless numbers. The analysis presented in this work can be readily applied to a general class of reversible reactions with volatile products and the methodology can be used to develop and design reactors for them. The approach and results presented here will be useful to establish optimal reactor configuration and design for urea alcoholysis reactions.